Is there temporal variation on solid waste stranding in mangroves? A case study in Ratones mangrove, Florianopolis, Brazil - Bianca Pinto Vieira; Dayse Dias; Elaine Mitie Nakamura; Tammy Iwasa Arai; Natalia Hanazaki (Biotemas)
Mangrove areas are decreasing around the world due to population increase. The most damaging activities include embankments, shrimp farming, and dumping of wastes. The temporal and spatial stranding patterns of solid waste are important to establish probable sources and understand their role in the dispersion of organisms through natural areas. In this study, we analyze temporal variation of solid waste stranding in Ratones mangrove, northwestern Santa Catarina Island (Brazil). Samplings were carried out monthly during one year in four different areas. In each area, two 50 m2 random plots were sampled per month. All solid waste strands on the plots were removed, quantified, and qualified. Plastic and nylon items (both made of petroleum) represented 80% of waste stranding. There were significant differences in temporal stranding with regard to plastic, but not to nylon. Wastes were found in all samples throughout the year, and some areas are more affected than others. Places with dense edges of Spartina alterniflora Loisel (Poaceae) seem to have less solid waste inside mangrove forest, perhaps due to the effect of grass acting as a mesh barrier. The results reflected concerns with conservation, considering that these coastal ecosystems are impacted by waste dumping throughout the year, with highest concentration within important nursery points.